Quality of life in patients after vestibular schwannoma surgery - Lazak, Jan; Betka, Jan; Zverina, Eduard; Vlasak, Ales; Bonaventurova, Marketa; Balatkova, Zuzana; Kana, Martin; Fik, Zdenek (Acta neurochirurgica, 2024)
AIM: To evaluate the most important factors of quality of life in patients after vestibular schwannoma surgery. MATERIALS AND METHODS: Patients with unilateral sporadic occurrence of vestibular schwannoma who underwent surgery via suboccipital-retrosigmoid approach were included in the prospective study (2018-2021). Patients after previous Leksell gamma knife irradiation (or other methods of stereotactic radiosurgery) were excluded. Quality of life was assessed using 10 validated questionnaires that were distributed preoperatively, 3 months and 1 year after the surgery. RESULTS: A total of 76 patients were included in the study, complete data were analysed in 43 of them (response rate 57%). Grade III and IV represented up to 70% of all tumors. Patients with larger tumors had a significantly higher risk of postoperative facial nerve paresis, liquorrhea and lower probability of hearing preservation. Patients with smaller tumors and those, who suffered from headaches before surgery had more frequent and severe headaches after surgery. Postoperative headaches were associated with higher incidence of anxiety and tinnitus. More frequent anxiety was also identified in patients with preoperative serviceable hearing who became deaf after surgery. Nevertheless, tinnitus and hearing impairment appeared to have less impact on overall quality of life compared to headaches and facial nerve function. CONCLUSION: According to our results, tumor size, postoperative function of the facial nerve and occurrence of postoperative headaches had the greatest influence on the overall postoperative quality of life in patients after vestibular schwannoma surgery.
Keywords: Humans; kvalita života; vestibulární schwannom; lidé; Tinnitus; Surgery; prospektivní studie; bolesti hlavy; Quality of life; Vestibular schwannoma; Prospective Studies; Headache; Quality of Life; Questionnaire; Neuroma, Acoustic; tinnitus